(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
This study aimed to determine the impact of human resources development on the effectiveness of crisis management among employees at private Jordanian Universities. The descriptive approach was adopted; By developing two tools to measure human resources development and the effectiveness of crisis management, The study community consisted of all employees of private Jordanian Universities in the capital, Amman, Within senior and middle management. According to the report of The Ministry of Higher Education for the year (2021), The number of private Universities in the capital reached (11). University, and due to the large size of the study community, (5) Universities were chosen because their geographical location is within the capital, Amman, and they have obtained the ISO (9001) certificate. (158) questionnaires were received, and after reviewing them, it was found that (3) questionnaires had incomplete answers, so they were excluded. Thus, The number of valid questionnaires for the purposes of analysis reached (155). The study recommended that Universities should adopt greater human resources development as a preliminary step to reduce the impact of crises they may face in the future, Encourage open communications, Transparency in dialogue, and accept complaints and suggestions between leaders and employees.